Pertanggungjawaban Notaris dalam Pembuatan Akta Pengikatan Jual Beli - Ni Kadek Sofia Septiarianti; I Nyoman Sumardika; Ni Gusti Ketut Sri Astiti (Fakultas Hukum, Universitas Warmadewa, 2020)
Notary public is a public official who has a noble position and in making every notarial deed a great responsibility so that no mistakes can occur. This study aims to determine the responsibility of a notary public in making a purchase agreement binding that has not been settled and to know the legal consequences of binding the purchase agreement that has not been paid in full. This research uses normative legal research methods. The data source used is the law or law as primary data (main data). The data analysis technique used is the argumentation technique and systemalization technique. The results of the analysis show that the responsibility of a notary public as a public official when making a deed of binding purchase agreement that is responsible for administrative law, civil law, criminal law and the code of ethics of the notary profession. Everything, of course, is based on the legal relationship that occurs between the land deed official and the parties facing when making the deed. Accountability for administrative sanctions is verbal warning, written warning, temporary dismissal, respectful dismissal even to disrespectful dismissal. Next to civil sanctions in the form of reimbursement or compensation and interest. Whereas a criminal sanction that can be accounted for by a notary/land deed official is if the fraud originated from the notary/land deed official itself for criminal sanctions can be given by first reviewing whether the notary / land deed official meets the contents of the formulation of the alleged crime. Apart from the three sanctions above, both in terms of legal, administrative, civil to criminal notary/land deed official which is certainly also responsible for conscious fulfillment of the notary code of ethics, which also makes the notary / land deed official responsible for sanctions in the form of: reprimand, warning, score, to dismissal from membership and dismissal with no respect.